Disfungsionalitas Humanitarianisme: Ekspektasi Kehadiran Resiprositas dalam Isu Vaksinasi Pengungsi dan Pencari Suaka di Indonesia - Pratama, Alexander Yudho; Debora, Debora; Elisa, Samuel; Araisya, Tristan Noa; Susila, Akbar Yudha (Universitas Diponegoro, 2021)
This paper analyzes the humanitarian act dysfunction in Indonesia, particularly emphasizing the disparity of refugee vaccination as a form of ignorance towards moral obligation. We argue that the presence of reciprocity expectation for Indonesia’s effort to vaccinate said group of people caused dysfunctionality. We approach the issue humanitarianly using the concept of global justice to explain the relevance of dysfunctionality and vaccine disparity for refugees as well as the moral obligation within the intermestic dimension. In line with the previously stated notion, the intermestic approach is also used as a catalyst for the re-observation of refugee accommodation strategy within the context of COVID-19 pandemic countermeasures. Indonesia’s neglect caused by the country’s reluctance becomes more understandable considering the small potential for politicization of these refugee vaccination efforts. Therefore, emphasizing on the rationalism of profit and loss aspect, the reciprocity motive is proven as vital reference through the attention given to the significance of actor’s roles and behavior, including state actors.